2022
DOI: 10.1111/tgis.12919
|View full text |Cite
|
Sign up to set email alerts
|

Are spatial patterns of Covid‐19 changing? Spatiotemporal analysis over four waves in the region of Cantabria, Spain

Abstract: This research approaches the empirical study of the pandemic from a social science perspective. The main goal is to reveal spatiotemporal changes in Covid‐19, at regional scale, using GIS technologies and the emerging three‐dimensional bins method. We analyze a case study of the region of Cantabria (northern Spain) based on 29,288 geocoded positive Covid‐19 cases in the four waves from the outset in March 2020 to June 2021. Our results suggest three main spatial processes: a reversal in the spatial trend, spre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…The study was conducted at the beginning of the multi‐country outbreak, so it reports only two types of emerging hotspots—consecutive hot spots and new hot spots—although this method can yield a maximum of 16 types. Furthermore, the absence of cold spots in the results reveals the increasing and active stage of MPXV around the world, against results obtained using this methodology in the COVID‐19 study, where many cold spots appeared (De Cos, 2022).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The study was conducted at the beginning of the multi‐country outbreak, so it reports only two types of emerging hotspots—consecutive hot spots and new hot spots—although this method can yield a maximum of 16 types. Furthermore, the absence of cold spots in the results reveals the increasing and active stage of MPXV around the world, against results obtained using this methodology in the COVID‐19 study, where many cold spots appeared (De Cos, 2022).…”
Section: Discussionmentioning
confidence: 57%
“…It determines if there is spatial clustering of high or low MPXV values based on significant spatiotemporal trends. Similarly, it was applied to COVID‐19 spread analysis, using polygons as defined locations (Chunbao et al., 2020; Syetiawan et al., 2022) and, more detailed spatially, using points of geocoded microdata (De Cos et al., 2021, 2022; Tokey, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Human mobility, connectivity, and transportation have been identified as key factors facilitating the virus' spread (14,(19)(20)(21)(22). Additionally, other reports have emphasized the importance of socioeconomic conditions, with socioeconomically deprived populations facing higher rates of exposure, incidence, and mortality (7,(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“… 14 Previous studies globally have demonstrated the effectiveness of spatial scan statistics in detecting hot spots of diseases such as cancers, drug poisoning, and infectious diseases (e.g., COVID-19). 13 , 15 , 16 , 17 Spatial cluster analysis could identify areas with higher-than-expected CC incidence to inform interventions to address the issue. Given the disproportionately high CC incidence in Texas and suboptimal uptake of HPV vaccination and CC screening, this study aimed to examine spatial clusters of CC incidence in Texas among women aged 30–64 years.…”
Section: Introductionmentioning
confidence: 99%